The influence of ecophysiographic determinants on the functional-spatial development of rural areas - a study of the village of Lubasz - Borucińska-Bieńkowska, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses selected issues concerning the influence of ecophysiographic determinants on functional-spatial and socio-economic development in rural areas. Ecological, economic and social processes that have been taking place for the past few decades are examined in the context of the development of local self-governments and transformation of economic processes into market oriented economy following socioeconomic changes in Poland.
Keywords: rural areas; functional-spatial development; economic; ecological processes; social processes; ecophysiography; obszary wiejskie; rozwój funkcjonalno-przestrzenny; gospodarka; ekologia; procesy społeczne; ekofizjografia